Problems Treatment Type II Diabetes Mellitus Patients with PCNE 9.1 and Correlation to Therapy Outcomes - Okky Intan Mawarni; Rina Herowati; Samuel Budi Harsono (MultiTech Publisher, 2023)
Drug-Related Problems in T2DM patients based on patient therapy patterns with or without comorbidities. DRP analysis is based on PCNE 9.1 guidelines analysing the domains causing problems in treatment, then bivariate data analysis (chi-square) to test the relationship between results and DRP type and continued with a multivariate test to see the connection between results and DRP type. The research results were three related variables related to DRPs and LOS, 15 cases of errors in drug selection, and eight instances of errors of treatment duration due to the absence of initiation of maintenance doses. Dose selection errors occurred in year 16, caused by an amount too low. It is recommended to research analysis prospectively so that the status of DRPs can be determined.